The diagnosis and management of inpatient hyponatraemia and SIADH. (28th June 2015) - Grant, Paul; Ayuk, John; Bouloux, Pierre‐Marc; Cohen, Mark; Cranston, Iain; Murray, Robert D.; Rees, Aled; Thatcher, Nicholas; Grossman, Ashley
Abstract Background Hyponatraemia is a very common medical condition that is associated with multiple poor clinical outcomes and is often managed suboptimally because of inadequate assessment and investigation. Previously published guidelines for its management are often complex and impractical to follow in a hospital environment, where patients may present to divergent specialists, as well as to generalists. Design A group of senior, experienced UK clinicians, met to develop a practical algorithm for the assessment and management of hyponatraemia in a hospital setting. The latest evidence was discussed and reviewed in the light of current clinical practicalities to ensure an up‐to‐date perspective. An algorithm was largely developed following consensus opinion, followed up with subsequent additions and amendments that were agreed by all authors during several rounds of review. Results We present a practical algorithm which includes a breakdown of the best methods to evaluate volume status, simple assessments for the diagnosis of the various causes and a straightforward approach to treatment to minimise complexity and maximise patient safety. Conclusion The algorithm we have developed reflects the best available evidence and extensive clinical experience and provides practical, useable guidance to improve patient care.